OPTIMALISASI PELAYANAN KESEHATAN BAGI NARAPIDANA RENTAN: STRATEGI UNTUK MEMPERBAIKI AKSES DAN KUALITAS - Subroto, Mitro; Hutabarat, Reyhan Dzaky (Ensiklopedia of Journal, 2024)
Abstract: This research addresses the optimization of health services for vulnerable inmate groups, highlighting the urgent need for improved healthcare access within correctional facilities. The study employs a mixed-methods approach, combining qualitative interviews with quantitative data analysis to assess existing health service frameworks and identify gaps. Findings indicate that vulnerable inmates face significant barriers to accessing adequate healthcare, including stigma, overcrowding, and insufficient resources. The research concludes that enhancing healthcare delivery systems and integrating community health services can significantly improve health outcomes for these populations. This study contributes to the discourse on prison healthcare reform, advocating for policies that ensure equitable access to health services for all inmates. Keywords: health services; vulnerable inmates; prison healthcare; optimization; access.